2013
DOI: 10.4049/jimmunol.1300908
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38α in T Cells Regulates the Intestinal Host Defense against Attaching and Effacing Bacterial Infections

Abstract: Intestinal infections by attaching and effacing (A/E) bacterial pathogens cause severe colitis and bloody diarrhea. Although p38α in intestine epithelial cells (IEC) plays an important role in promoting protection against A/E bacteria by regulating T cell recruitment, its impact on immune responses remains unclear. In this study, we show that activation of p38α in T cells is critical for the clearance of the A/E pathogen Citrobacter rodentium. Mice deficient of p38α in T cells, but not in macrophages or dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Induction of cytokine mRNA by ConA was significantly reduced in p38α-deficient leukocytes (Figure 4C). Consistently, our study also indicated that TCR-induced expression of cytokine genes was also significantly reduced in p38α-deficient T cells compared with control cells (21) (data not shown). However, induction of cytokine mRNA by α-GalCer did not differ between control and p38α-deficient leukocytes (Figure 4D), implying that p38α does not directly regulate the induction of inflammatory cytokine expression in NKT cells, but is involved in the post-transcriptional regulation of gene expression as shown previously (29).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Induction of cytokine mRNA by ConA was significantly reduced in p38α-deficient leukocytes (Figure 4C). Consistently, our study also indicated that TCR-induced expression of cytokine genes was also significantly reduced in p38α-deficient T cells compared with control cells (21) (data not shown). However, induction of cytokine mRNA by α-GalCer did not differ between control and p38α-deficient leukocytes (Figure 4D), implying that p38α does not directly regulate the induction of inflammatory cytokine expression in NKT cells, but is involved in the post-transcriptional regulation of gene expression as shown previously (29).…”
Section: Resultssupporting
confidence: 83%
“…Additionally, TUNEL assay indicated that induction of apoptosis was significantly reduced in the liver tissue of p38α ΔT mice (Figure 1D). Because T and NKT cells play an important role in ConA-induced liver damage (26-28), and Lck-cre-mediated deletion of p38α was observed in T cells as well as NKT cells of hepatic leukocytes (Supplemental Figure 1) (21,29), our results indicate that p38α promotes the activation of T and NKT cells in ConA-induced hepatitis.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations